SCRUTINIZING PAPUAN EFL STUDENTS’ READING COMPREHENSION IN THE LIGHT OF METACOGNITIVE STRATEGIES - Onni Tabuni; Reiner J. H. G. Lawalata; Abel Yohanis Romrome (STKIP Persada Khatulistiwa Sintang, 2026)
Reading comprehension is a crucial skill for English as a Foreign Language (EFL) learners, yet many students in Papua Pegunungan struggle with it due to low literacy levels, limited motivation, and ineffective reading strategies. This study investigated the role of metacognitive strategies namely planning, monitoring, and evaluating in enhancing EFL students’ reading comprehension. A mixed-method design was employed, involving 35 undergraduate students at STKIP Kristen Wamena. Data were collected through reading comprehension tests, the Metacognitive Awareness of Reading Strategies Inventory (MARSI), and semi-structured interviews. Quantitative findings revealed that most students performed at a medium level of comprehension (62.9%), with difficulties in higher-order skills such as inference and integration. Students reported moderate use of metacognitive strategies (M=3.2), applying monitoring most frequently, while planning and evaluation were less evident. Correlation analysis confirmed a significant positive relationship between strategy use and comprehension, particularly monitoring (r= 0.62, p < 0.01). Qualitative data indicated that high-performing students consistently monitored and evaluated their understanding, while low achievers read reactively without clear goals. The study concluded that explicit training in metacognitive strategies, especially planning and evaluation, alongside efforts to foster reading motivation, is essential for improving comprehension outcomes among Papuan EFL learners.